Recreational sector is the dominant source of fishing mortality for oceanic fishes in the Southeast United States Atlantic Ocean - Kyle W. Shertzer; Erik H. Williams; Joseph Kevin Craig; Eric E. Fitzpatrick; Nikolai Klibansky; Katie I. Siegfried (Fisheries Management and Ecology, 2019)
Recreational fishing is increasingly recognised as an important source of mortality for marine fish populations. In the United States, estimates of marine recreational catch and effort were recently revised for the time period 1981 and beyond, and for many species, the revised estimates were substantially higher than the original values. Here, the proportion of total landings that came from the recreational sector in the Southeast US Atlantic was quantified. The proportions for 22 oceanic species and for all species combined were computed, using a full time series of landings (1981–2016) and a more recent time series (1999–2016). For the full and recent time series, landings of most species (15/22 and 17/22, respectively) were dominated by the recreational sector. For all species combined, 71% of landings in the full time series were from the recreational sector, and 76% in the recent time series. Trend analysis indicated that most species had a stable or increasing proportion of landings from the recreational sector. In addition, stock assessments were conducted on four species, and the catch revisions increased the estimated scale of abundance and, in some cases, affected stock or fishery status. This work underscores the importance of recreational fishing for marine resource management.